Becoming a matter of veterinary concern - Smith, Rebecca; Pinchbeck, Gina; McGowan, Catherine; Ireland, Joanne; Perkins, Elizabeth (Frontiers in Veterinary Science, 2024)
Horses in Great Britain are living into increasingly older age and are often regarded as friends or family members by their owner. The horse is reliant on their owner to meet their needs and this paper discusses how horse owners frame an issue that becomes a matter of veterinary concern within the context of the older horse. Qualitative methods were used to explore the experiences of owners and veterinarians. Data were collected and analysed using a grounded theory approach during the period 2019–2022. Analysis identified that owners undertook an ongoing and iterative process of assessment, monitoring and decision making in relation to the animal and any changes they observed. Matters that became a veterinary concern required the owner to formulate the issue as something that fell within the knowledge domain of the veterinarian. Veterinarians had a medicalised view of older horse health and their perspectives on socially acceptable care were shaped by their understanding of species-specific needs, and whether owners were providing appropriately for those needs. The formulation of a matter of veterinary concern was itself shaped by an owner’s experiential knowledge of both veterinary matters and their horse. The extent to which owners felt like they and their individual horse mattered during interactions with veterinarians affected whether they adopted veterinary advice and the nature of future veterinary employment. Findings demonstrate how matters of health, disease, and the role of professionalised forms of medical knowledge, are not static but constantly changing and interacting over time. An issue that became a matter of veterinary concern was contextual, and rooted in individual relationships. The significance of veterinarian-owner interactions in shaping future consumption of veterinary health care may be underestimated.